Bariatric Surgery: Latest Advances and Prospects - Benaiges Boix, David (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint is a compilation of cutting-edge knowledge in the field of bariatric surgery. It addresses the growing obesity epidemic and provides in-depth insights into the latest innovations in bariatric surgery and its future prospects. The content of the work includes a comprehensive review of modern surgical techniques. Additionally, it explores key aspects of preoperative assessment, postoperative follow-up, and the management of potential complications. The reprint highlights the benefits of bariatric surgery in improving the health and quality of life of morbidly obese patients. The reprint also addresses emerging trends in research and technology, such as robotic surgery and gene therapy, which hold the promise of further revolutionizing the field.